Pengaruh Bauran Pemasaran Terhadap Tingkat Penjualan Motor Yamaha Mio M3 Pada PT. Hasjrat Abadi Cabang Tumpaan - Tinungki, Deysy Deyby; Tampi, Johny R. E.; Punuindoong, Anneke Y. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
This research is purposeful to determine the extent of the effect of marketing mix on the level of sales. This research useda quantitative method. The subjects in this research were the consumers at PT. Hasjrat Abadi Branch of Tumpaan. The object of this research were the marketing mix and the level of sales at PT.Hasjrat Abadi Branch of Tumpaan. Population in this research were consumers ofÂ  PT. Hasjrat Abadi Branch of Tumpaan, comprised of 437 people who have been netted for 2 months, with a sample of 81 respondents. Data collection techniques were interview, observation, documentation, and questionnaire. Analysis of data used descriptive analysis, validity and reliability, the analysis of the correlation coefficient, determination coefficient, multiple correlation and linear regression. Hypothesis test used was T test (partial test) and F test (simultaneous test). From the results of data analysis found that the partial product of positive and significantly affect on the level of sales Yamaha Mio M3 Motorcycle at PT. Hasjrat Abadi Branch of Tumpaan. Product is the most dominant variable affecting on the level of sales. Prices partially positive and significant effect on the level of sales Yamaha Mio M3 Motorcycle at PT. Hasjrat Abadi Branch of Tumpaan. Partially promotion of positive and significant effect on the level of sales Yamaha Mio M3 Motorcycle at PT. Hasjrat Abadi Branch of Tumpaan. The place is partially positive and significant effect on the level of sales Yamaha Mio M3 Motorcycle at PT. Hasjrat Abadi Branch of Tumpaan. Simultaneously the product, price, promotion, and place a significant effect on the level of sales Yamaha Mio M3 Motorcycle at PT. Hasjrat Abadi Branch of Tumpaan. The company needs to sustain the product quality, the price of conformity, innovation in promoting and all is place in an effort to boost the level of sales.Keywords : Marketing Mix, The Level of Sales.